Bridging the urban energy divide: equity-focused transition pathways for sub-Saharan African cities - Yongoua Nana, Joel (Department of Chemical Engineering, 2025)
This thesis examines how alternative urban energy transition pathways in Sub-Saharan Africa could simultaneously address the imperatives of equitable energy access and use across different income groups, while meeting other development and sustainability goals. Through detailed analysis of six cities - ranging from metropolitan centres to smaller towns - the research provides new insights into the patterns and drivers of energy inequalities in African urban contexts. The study makes several contributions to knowledge. First, it presents the first comprehensive, multi-city analysis of urban energy consumption and emissions across key economic sectors in African cities. Key findings highlight that urban energy profiles in Sub-Saharan Africa exhibit far greater heterogeneity than often recognized. Results from the scenario analysis also showed that this heterogeneity results in varied equity outcomes even when the study cities were subjected to the same policy interventions, therefore demanding more context-specific approaches to urban energy policy design. The research also identifies electricity use as uniquely significant among energy carriers, showing both the strongest correlation with GDP and typically the most unevenly distributed across household quintiles. Second, the thesis makes relevant methodological contributions through the development and implementation of the Urban Household Energy Model (UHEM), a transparent bottom-up modelling framework custom-designed to analyse household energy inequalities in African urban contexts. Through extended application of the Gini coefficient and Lorenz curve to previously inaccessible municipal datasets, the research provides new evidence that household energy use inequalities consistently show significantly lower magnitudes than income inequalities, suggesting that energy's status as a fundamental need creates a "floor effect" in consumption patterns. This, however, does not extend to electricity use, which shows markedly higher inequalities, in some cases even exceeding income inequality. Third, the research advances both scholarly understanding and practical policy development through its assessment of energy transition policies. Analysis of current policy commitments (Stated Energy Policies Scenario - STEPS) reveals that despite often lacking clearly actionable measures on equity, these interventions could achieve meaningful reductions in household energy use inequalities, with clean cooking and electricity access interventions typically the most powerful levers for reducing household energy inequalities. The research further examines two alternative scenarios - Blues and Harmony - specifically designed through an equity lens. The Blues scenario, emphasizing bottom-up, community-driven approaches, demonstrated more significant outcomes across most metrics, achieving substantially greater reductions in household energy use inequality than STEPS and Harmony across several study cities. However, the findings have revealed a non-linear relationship between clean energy access and inequality reduction, suggesting diminishing returns beyond certain thresholds of clean energy adoption in advancing equity goals. Additionally, analysis of hypothetical income redistribution policies suggests their potential complementary role in reducing energy inequalities, achieving higher outcomes to energy-focused policies alone in some of the studied cities. These findings have important implications for urban energy policy design in Africa. While current stated policies show promise in reducing overall energy and emissions inequalities, achieving more equitable outcomes would benefit from: (1) decentralizing energy access and governance and enabling regulatory frameworks, (2) building local research expertise and data infrastructure v to support context-specific planning, (3) enabling economic equity through policies that encourage community wealth creation and local ownership of energy assets, and (4) strengthening municipal authority while fostering strategic coalitions across governance levels.